Komunikasi Interpersonal Dalam Pergaulan Remaja Broken Home Di Kecamatan Mataram - I Gusti Ayu Sri Wulandari; Ida Bagus Made Arjana; I Ketut Putu Suardana (BICARA: Jurnal Ilmu Komunikasi, 2023)
This study aims to examine the form, process, and impact of Interpersonal Communication in the association of broken home youth in the Mataram District. Thus the formulation of the research problem is (1) What is the form of interpersonal communication in the association of broken home youth in the Mataram District? (2) What is the process of interpersonal communication for broken home youth in Mataram District? (3) What is the impact of interpersonal communication on broken home adolescents in Mataram District? This research was studied using qualitative methods and a case study approach. Data were collected by observation, interview and documentation techniques. Then analyzed with data reduction techniques, data display and data verification. The findings in this study are supported by three theories namely, self-disclosure theory (Jonshon), self-adjustment theory (Schneider), and communication accommodation theory (Howard Giles). The results of this study explain that interpersonal communication that occurs in broken home adolescent associations runs as usual like teenagers in general and there are forms of verbal and non-verbal communication, through oral communication in which there are communicators and communicants and produces the impact of interpersonal communication, namely established communication active among broken home teenagers and other teenagers in general. And in this study there are findings that active communication also occurs in broken home adolescents who have the same destiny based on mutual understanding of each other regarding the family situation they are facing. As for suggestions by the author for relatives, teachers, and the community, namely to be more sensitive and pay attention to teenagers who experience broken homes.